2005
DOI: 10.1093/pasj/57.3.481
|View full text |Cite
|
Sign up to set email alerts
|

Solar-Cycle Variation of Magnetic Helicity in Active Regions

Abstract: The hemispheric sign rule of helicity and its long-term variation were studied. The data were obtained from the Solar Flare Telescope at Mitaka and the 65-cm solar telescope at Okayama. The data covered the period of 1983–2001, from the declining phase of solar cycle 21 to the rising phase of cycle 23. Although the hemispheric sign rule of helicity generally holds, we also found significant time variations in the yearly values of helicity during the observation period. The hemispheric sign rule of helicity is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
51
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 16 publications
13
51
1
1
Order By: Relevance
“…More detailed calculations of helicity can be done by using such poloidal field distributions instead of using the simple boundary condition (24). Since some groups have started reporting on the possible cycle variation of helicity on the basis of the observational data (Bao et al 2000;Hagino & Sakurai 2005), such calculations may become relevant in future when more detailed observational data are available.…”
Section: Resultsmentioning
confidence: 99%
“…More detailed calculations of helicity can be done by using such poloidal field distributions instead of using the simple boundary condition (24). Since some groups have started reporting on the possible cycle variation of helicity on the basis of the observational data (Bao et al 2000;Hagino & Sakurai 2005), such calculations may become relevant in future when more detailed observational data are available.…”
Section: Resultsmentioning
confidence: 99%
“…Case (b) shows that the sign rule reverses its sense near the activity minimum periods, as was advocated by Hagino & Sakurai (2005). Choudhuri et al (2004) explained such a reversal by the combination of the dynamo-generated new toroidal field and the old poloidal field from the previous cycle.…”
Section: Discussionmentioning
confidence: 76%
“…For reference, Longcope et al (1998) Bao et al (2000) used α best and H c , and Pevtsov et al (2008) used α best . The conclusion of Pevtsov et al (2008), in which Hagino and Sakurai were coauthors, is against Hagino & Sakurai (2005), but the former used α best and the latter adopted α…”
Section: Proxies Of Helicitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the helicity parameter H c shows a weaker opposite hemisphereic preference in the new solar cycle. Hagino and Sakurai (2005) found that although the hemispheric sign rule of helicity generally holds, it is found significant time variations in the yearly values of helicity during the observation period. The hemispheric sign rule of helicity is satisfied in the solar maximum phase, but may not be so in the solar minimum phase.…”
Section: Helicity and Solar Flare-cmesmentioning
confidence: 85%